The criteria for determination of refugee status in International Law: a critical appraisal - Ishan Jan, Mohammad Naqib (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
he twenty first century has witnessed disastrous events in different parts of the world causing millions of people to leave their countries of origin hoping to seek refuge and protection against ‘persecution’ from other countries. However, their hopes are often shuttered when their status as refugees is not recognised and thereby effectively denied protection which international refugee law accord to them. One of the reasons for inaccessibility to refugee status in most of the host states is the adoption of restrictive interpretation of the criteria for the determination of refugee status that are laid down in the 1951 Convention relating to the Status of Refugees as amended by its 1967 Protocol. As will be discussed in this paper, if states have adopted a broader interpretation of these criteria many of the asylum seekers would face no problem in acceding to refugee status and the benefits that accrue from it. Broad interpretation of these criteria, as this paper advocates, would be inline with humanitarian idealism of international refugee law, provide a pragmatic solution to the problem faced by millions of desperate people and uphold the spirit and protective nature of international refugee law.